2022
DOI: 10.1016/j.jbc.2022.101604
|View full text |Cite
|
Sign up to set email alerts
|

MCU (mitochondrial Ca2+ uniporter) makes the calcium go round

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In mammals, mitochondrial translation occurs in mitoribosomes, and these ribosomes produce proteins that play a part in oxidative phosphorylation [ 48 , 50 , 51 ]. As previously pointed out, there is a relation between SOCE and calcium regulation in mitochondria [ 52 , 53 , 54 , 55 ]. Our pathway enrichment results also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, mitochondrial translation occurs in mitoribosomes, and these ribosomes produce proteins that play a part in oxidative phosphorylation [ 48 , 50 , 51 ]. As previously pointed out, there is a relation between SOCE and calcium regulation in mitochondria [ 52 , 53 , 54 , 55 ]. Our pathway enrichment results also support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, Yoast et al, found that MCU deletion led to increased Ca 2+ -dependent inactivation of CRAC channels and reduced Ca 2+ currents through the channels. Yet, the net result was an overall amplification of cytosolic Ca 2+ signaling caused by elimination of mitochondrial Ca 2+ buffering in the absence of MCU ( Yoast et al, 2021 ; Walters and Usachev, 2022 ). Although this effect was documented in non-excitable cell lines, given that CRAC channels and MCU are present in the nervous tissues, it is predicted that a similar mechanism could contribute to the regulation of neuronal excitability ( Walters and Usachev, 2022 ).…”
Section: Mitochondrial Ca 2+ Cycling In Neuronal F...mentioning
confidence: 99%
“…Meanwhile, mCa 2+ in its physiological state is known to activate three major mitochondrial matrix dehydrogenases, namely, pyruvate dehydrogenase (PDH), isocitrate dehydrogenase (ICDH), and α-KGDH. The regulation of these three key enzymes by Ca 2+ has a strategic task in coordinating cellular workload and ATP generation [ 180 , 181 , 182 ]. Thus, cancer cells meet their energy demands by the activation of TCA cycle dehydrogenases through increased mCa 2+ uptake [ 183 ].…”
Section: Mitochondrial Metabolism and Mirnamentioning
confidence: 99%